Análisis del liderazgo de los gerentes de las empresas de la provincia de El Oro. - Pineda Ramón, Jose Abel; Briones Samaniego, Angelica Del Rocio (Universidad Técnica de Machala, 2022)
The present investigation will focus on the analysis of the leadership of the Managers since it is aone of the least investigated topics, but at the same time very relevant in the business field this being a fundamental pillar for the development and performance of executive activities such as operations, in addition, the excellent management of human talent and to position itself as one of the the best nationally and internationally, since El Oro is one of the provinces with the highest economic activity, among them the commercial, industrial and services, in addition to agriculture, fishing and livestock, causing the emergence of various economic entities.
La presente investigación se enfocará en el análisis del liderazgo de los Gerentes ya que es un uno de los temas menos investigado, pero a la vez muy relevante en el ámbito empresarial siendo ello un pilar fundamental para el desarrollo y desempeño de actividades ejecutivas como operativas, además, el excelente manejo del talento humano y logar posicionarse como una de las mejores a nivel nacional e internacional, ya que El Oro es una de las provincias con mayor actividad económica, en entre ellas se destacan las actividades comerciales, industriales y de servicios, además de, la agricultura, pesca y ganadería provocando surgimiento de diversas entidades económicas.
Keywords: LIDERAZGO; EMPRESAS